Investigation the biological activities and the metabolite profiles of endophytic fungi isolated from Gundelia tournefortii L. - Mostafa Ebadi; Fatemeh Ahmadi; Hossein Tahmouresi; Mohammad Pazhang; Saeed Mollaei (Scientific Reports, 2024)
Abstract Endophytic fungi are microorganisms that are considered as a potential source of natural compounds, and can be applied in various industries. The aims of this research were molecular identification of endophytic fungi isolated from the Gundelia tournefortii stems, and investigation their biological activities as well as phenolic and fatty acid profile. Surface sterilized stems of G. tournefortii were placed on potato dextrose agar (PDA) to isolate the fungal endophytes. Genomic DNA was extracted by CTAB method, and PCR amplification was performed by ITS 1 and ITS 4 as primers. The enzyme production of endophytic fungi was determined based on the formation of a clear zone that appeared around the colonies of fungus. The anti-oxidant activity was evaluated by measuring the amount of free radicals DPPH. Also, the total phenol and flavonoid contents were measured obtained by Folin-Ciocalteu and aluminum chloride colorimetric methods, respectively. Moreover, the separation and identification of phenolic acids and fatty acids were done by HPLC and GC, respectively. Phylogenetic analysis was done based on the Internal Transcribed Spacer (ITS) region, and five isolates were identified as following: Aspergillus niger, Penicillium glabrum, Alternaria alternata, A. tenuissima, and Mucor circinelloides. Evaluation of the enzymatic properties showed that P. gabrum (31 ± 1.9 mm), and A. niger (23 ± 1.7) had more ability for producing pectinase and cellulase. The anti-oxidant activity of isolates showed that A. alternata extract (IC50 = 471 ± 29 µg/mL) had the highest anti-oxidant properties, followed by A. tenuissima extract (IC50 = 512 ± 19 µg/mL). Also, the extract of A. alternata had the greatest amount of total phenols and flavonoids contents (8.2 ± 0.4 mg GAL/g and 2.3 ± 0.3 mg QE/g, respectively). The quantification analysis of phenolic acid showed that rosmarinic acid, para-coumaric acid, and meta-coumaric acid (42.02 ± 1.31, 7.53 ± 0.19, 5.41 ± 0.21 mg/g, respectively) were the main phenolic acids in the studied fungi. The analysis of fatty acids confirmed that, in all fungi, the main fatty acids were stearic acid (27.9–35.2%), oleic acid (11.3–17.3%), palmitic acid (16.9–23.2%), linoleic acid (5.8–11.6%), and caprylic acid (6.3–10.9%). Our finding showed that endophytic fungi are a source of bioactive compounds, which could be used in various industries. This is the first report of endophytic fungi associated with G. tournefortii, which provides knowledge on their future use on biotechnological processes.